2017
DOI: 10.1038/srep46301
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adeno-Associated Virus-Mediated Expression of Methamphetamine Antibody Attenuates Methamphetamine-Induced Hyperactivity in Mice

Abstract: Methamphetamine (Meth) is one of the most frequently abused drugs worldwide. Recent studies have indicated that antibodies with high affinity for Meth reduce its pharmacological effects. The purpose of this study was to develop a technique for virus-based passive immunization against Meth effects. We generated a recombinant adeno-associated virus serotype-8 vector (AAV-MethAb) carrying the gene for a Meth-specific monoclonal antibody (MethAb). Infection of 293 cells with AAV-MethAb resulted in the expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Interestingly a similar study with an AAV delivered anti-METH IgG using the same variable sequence as scFv6H4 showed conflicting serum results to those we observed. [ 23 ] In this study, they reported a 23% decrease in METH in the serum of their treated mice compared to mice administered PBS 10 minutes after a 1 mg/kg METH ip dose. This is an unusual observation, as antibodies against drugs of abuse have been shown to have small volumes of distribution and partition their targets in the serum.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly a similar study with an AAV delivered anti-METH IgG using the same variable sequence as scFv6H4 showed conflicting serum results to those we observed. [ 23 ] In this study, they reported a 23% decrease in METH in the serum of their treated mice compared to mice administered PBS 10 minutes after a 1 mg/kg METH ip dose. This is an unusual observation, as antibodies against drugs of abuse have been shown to have small volumes of distribution and partition their targets in the serum.…”
Section: Discussionmentioning
confidence: 77%
“…Mice injected with the recombinant virus started producing antimethamphetamine antibodies starting at week 2, peaked at week 7, and was maintained at a high, steady level up until the endpoint of the study at week 29 61 . As expected, the peripheral antibodies produced by the recombinant virus in vivo reduced methamphetamine levels in the mouse brains and sera, as well as reduced locomotor behavior (horizontal activity, total distance traveled, movement number, stereotype count, stereotype number, and vertical movement number) induced by methamphetamine in the mouse model 61 . In this recent study, infecting mice with the recombinant virus did not elicit any immunological abnormalities in terms of cytokine levels and lymphocyte counts 61 .…”
Section: Passive Immunizationmentioning
confidence: 99%
“…It is also a serine protease inhibitor which circulates in healthy individuals and is usually increased in most inflammatory diseases such as ACS (10). The normal AAT plasma level is 1.04 g/l or ~20 µM (11) and this may increase by 3-5-fold when an inflammatory reaction occurs (12).…”
Section: Introductionmentioning
confidence: 99%